PROFIL LITERASI SAINS SISWA SMP SEBAGAI DASAR PENGEMBANGAN KETERAMPILAN MENELITI DALAM PEMBELAJARAN IPA - Sri Wahyuni; Eko Hariyono; Beni Setiawan (SPEKTRA: Jurnal Kajian Pendidikan Sains, 2026)
Scientific literacy is an essential competency in science education, yet its integration with research skills remains limited in classroom practice. This study aims to analyze the scientific literacy profile of junior high school students and examine its relationship with research skills. A descriptive quantitative approach was conducted with 88 eighth-grade students selected through purposive sampling. Data were collected using a multiple-choice test based on an international scientific literacy framework, supported by limited interviews. The findings show that students’ scientific literacy is at a moderate level, with stronger performance in explaining scientific phenomena, while abilities in evaluating investigations and using scientific evidence are relatively low. Furthermore, scientific literacy aligns with stages of research skills, where students demonstrate adequate ability in identifying problems but face difficulties in analyzing data and drawing conclusions. These results suggest the need for instructional designs that emphasize inquiry and active investigation to better support the development of both scientific literacy and research skills.